Quality Improvement in Sweet Red Wines Through an Alternative Grape-Drying System - Marquez, A.; Serratosa, M.P.; Merida, J. (South African Journal of Enology and Viticulture, 2013)
A sensorial analysis was undertaken and the colour parameters and phenolic profile were measured for two types of Andalusian sweet red wines. Two wines types were studied, i.e. commercial and alternative wines elaborated with musts from grapes obtained by traditional sun drying and by chamber drying under controlled temperatures respectively. Results show that the alternative wines obtained in this study were analytically closer to typical red wines in their lower concentration of browning compounds, a high contribution of red and blue colour, and hence having a more suitable hue than the traditional sweet wines. Furthermore, the alternative wines were the richest in monomeric anthocyanins, flavan-3-ols and flavonols, which give these wines their antioxidant properties. Their sensorial characteristics were accepted by consumers, which means that the alternative grape-drying system improves the quality of sweet red wines relative to those obtained by the traditional method.